Refrigeration - Ekren, Orhan (IntechOpen, 2017)
In the beginning, the sole purpose of utilization of the refrigeration was to conserve food (BC 1100). But today in our daily life, refrigeration is one of the necessary areas for the aim of not only food conservation but also comfort, industrial production, electronic equipments' performance, safe and proper operation of telecommunication stations and computer rooms, space studies, etc. The importance and wide application range of the refrigeration require new techniques and researches. In this respect, the scope and topics of the book are: Multistage refrigeration cycle analysis, Electrocaloric cooling method, Food chilling-freezing methods and equipments, CFD modeling of airflow in the display cabinet, Industrial application of refrigeration, Energy-efficient air-conditioning system comparison, Capacity modulation methods for energy-efficient refrigeration.